Mobile Cultures : New Media in Queer Asia - Yue, Audrey; Martin, Fran, 1971-; Berry, Chris, 1959 April 28- (Book collections on Project MUSE., 2003)
A collection of essays on the uses of new media in the formation of East Asian and Pacific queer identities.